MANAJEMEN STRATEGI PEMASARAN PENDIDIKAN UNTUK MENINGKATKAN DAYA SAING SMA NEGERI 1 BANDAR DUA - Muhsin Muhsin; Sukarman Purba; Irsan Rangkuti (Universitas Jabal Ghafur, 2023)
Education marketing management is an activity of analyzing, planning, implementing, and evaluating. The objectives of this study are to determine (1) education marketing planning at SMA Negeri 1 Bandar Dua, (2) to determine the implementation of education marketing at SMA Negeri 1 Bandar Dua, (3) to determine the evaluation of education marketing at SMA Negeri 1 Bandar Dua. In this study, researchers used qualitative methods in a descriptive and analytical way. Furthermore, the data were taken with data collection techniques through observation, interviews, and documentation. Then, the research subjects were the principal of SMA Negeri 1 Bandar Dua and the Head of Public Relations of SMA Negeri 1 Bandar Dua. Furthermore, according to the results of the research obtained, educational marketing management needs to be carried out with good management, be it planning, implementation, and marketing evaluation. Planning at the school is carried out by holding meetings with related fields for programs that will be implemented in the future, designing time, place, and target. Then the implementation of education marketing is carried out by means of a promotion system, distributing brochures, and conducting socialization to targeted schools. Finally, the evaluation stage is carried out by controlling every semester, and seeing whether it is in accordance with the initial plan or not.Keywords : Marketing Strategy Management, Competitiveness, New student interest